2018
DOI: 10.1590/0100-5405/167203
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidas no manejo da ferrugem da soja, processos fisiológicos e produtividade da cultura

Abstract: RESUMO Atualmente, as recomendações de manejo para a ferrugem asiática da soja (FAS) têm sido baseadas na aplicação de fungicidas protetores em mistura com triazóis, estrobilurinas e carboxamidas. Desta forma, objetivou-se avaliar se o incremento de produtividade proporcionado pela aplicação de mancozebe é devido unicamente à ação fungicida do produto ou à alguma alteração fisiológica na planta e qual alteração seria esta. O experimento foi conduzido no período de março a junho de 2015, na estação experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
(5 reference statements)
2
7
0
1
Order By: Relevance
“…In a study conducted by Alves and Juliatti (2018), they confirmed that the combination of the same compounds used in this study (Piraclostrobin + Fluxapiroxade + Prothioconazole + Trifloxystrobin + Cyproconazole + Picoxystrobin) provided ample control of pathogens when added with mancozeb. In this study it was not necessary to use mancozeb for the whole pathogen population to be contained.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 76%
“…In a study conducted by Alves and Juliatti (2018), they confirmed that the combination of the same compounds used in this study (Piraclostrobin + Fluxapiroxade + Prothioconazole + Trifloxystrobin + Cyproconazole + Picoxystrobin) provided ample control of pathogens when added with mancozeb. In this study it was not necessary to use mancozeb for the whole pathogen population to be contained.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 76%
“…Products composed of mixtures of triazoles, strobilurins and carboxamides have been the most widely used, what has led to the emergence of resistant populations of P. pachyrhizi (Godoy 2012). However, it is important to know the effects of the application of protective fungicides, such as mancozeb, on the physiological processes of plants and in the absence of Asian soybean rust (Alves & Juliatti 2018).…”
Section: Abstract Resumomentioning
confidence: 99%
“…Rios et al (2010), when artificially inoculating soybean plants with P. pachyrhizi uredospore, observed reductions in the protective and healing effects of fungicides as the applications were performed farther from inoculation. Alves and Juliatti (2018) in a work with the application of mancozeb and systemic fungicides concluded that the effect of adding protective fungicides with systemic fungicides varied according to the interaction between these molecules. However, the applications made by Alves and Juliatti (2018) started when the plants were in the R1 stage, and, in general, the preventive applications of fungicides are more efficient in controlling rust compared to eradicating applications (AUGUSTI et al, 2014), and the protective fungicides, when applied under ideal conditions, remain on the leaves and inhibit the germination of spores in a range of hosts and in a non-specific way, acting in several fungal cell sites (REIS, 2014;ZAMBOLIM et al, 2008), therefore, being more efficient when applied preventively.…”
Section: Resultsmentioning
confidence: 99%